Analisis Etos Kerja Islam Pada UMKM Rumah Produksi Olis Kota Jambi - Suri Oktiana; Eja Armaz Hardi; Marissa Putriana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
ork ethic is one of the most important and influential components of enterprise or business. Competiton in the business currently very rapidtherefore businesses are required to improve the quality of human resources effectively and effeciently. According to Islam, work ethic is a Muslim’s belief that work is a form of worship that obtains the approval of Allah SWT. This research aims to describe the analysis of the Islamic work ethic in the Olis Production House MSMEs in Jambi City. The data collection technique in the research used the interview method from 9 respondents, consisting of the owner and all employees at the Olis Production House MSMe Jambi City.Data collection techniques use qualitative methods for primary and secondary data. The results of this research can be concluded that the Islamic work ethic at the Olis Production House MSME employees has implemented several work ethics in accordance with Islamic principles, namely by adopting an attitude of responsibility,working sincerely honestly, and having pure morals. However, there is also one Islamic work ethic that has been implemented by employees at the Olis Production House MSME, namely discipline and don’t value time.